2018
DOI: 10.1136/heartjnl-2018-313682
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output changes from prior to pregnancy to post partum using two non-invasive techniques

Abstract: ObjectivesWe aimed to describe cardiac output (CO) trend from prepregnancy to post partum using an inert gas rebreathing (IGR) device and compare these measurements with those obtained by a pulse waveform analysis (PWA) technique, both cross-sectionally and longitudinally.MethodsNon-smoking healthy women, aged 18–44 years, with body mass index <35 were included in this prospective observational study. CO measurements were collected at different time points (prepregnancy, at four different gestational epochs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…33e42 Our group, using different methodologies, recently reported that a rise in the peak cardiac output occurred earlier and more modestly than previously thought (þ1.05 L/min or 17.5% above the prepregnancy value at 15.2 weeks' gestation as measured using the inert gas rebreathing technique; þ0.47 L/min or 7.7% above the prepregnancy value at 10.4 weeks' gestation as measured using the pulse wave velocity). 42 As the product of stroke volume and heart rate, the cardiac output increase is driven more by the progressive rise in the heart rate, which peaks in the third trimester (20% e24% higher than the prepregnancy value), than stroke volume (13% increase from the prepregnancy value in the second trimester). 32,40,43 The decrease in the peripheral vascular resistance with gestational age is associated with a reduction in the uterine artery and fetal umbilical Doppler impedance.…”
Section: Ajogorgmentioning
confidence: 99%
See 1 more Smart Citation
“…33e42 Our group, using different methodologies, recently reported that a rise in the peak cardiac output occurred earlier and more modestly than previously thought (þ1.05 L/min or 17.5% above the prepregnancy value at 15.2 weeks' gestation as measured using the inert gas rebreathing technique; þ0.47 L/min or 7.7% above the prepregnancy value at 10.4 weeks' gestation as measured using the pulse wave velocity). 42 As the product of stroke volume and heart rate, the cardiac output increase is driven more by the progressive rise in the heart rate, which peaks in the third trimester (20% e24% higher than the prepregnancy value), than stroke volume (13% increase from the prepregnancy value in the second trimester). 32,40,43 The decrease in the peripheral vascular resistance with gestational age is associated with a reduction in the uterine artery and fetal umbilical Doppler impedance.…”
Section: Ajogorgmentioning
confidence: 99%
“…51 In a normal pregnancy, the pulse wave velocity, which is a measurement of the blood flow velocity in the aorta, and augmentation index, a parameter that provides a measure of the pressure wave reflection through the muscular arterial tree, decrease from the first weeks of pregnancy and reach the lowest value in the second trimester, followed by a rise during the third trimester. 40,42,46,52,53 A gradual return to the prepregnancy cardiovascular profile occurs postpartum, with different parameters restoring at different rates. The cardiac output remains significantly higher than the prepregnancy value for up to 1 year postpartum (þ12% from the prepregnancy values) and a similar behavior is observed for the left ventricular mass, whereas the peripheral vascular resistance is reported to be lower than or similar to the prepregnancy value depending on the study.…”
Section: Scale On Left Axismentioning
confidence: 99%
“…In previous investigations, determination of ̇ using non-invasive methods in pregnant women have highlighted: i) that there are inevitable differences between techniques, ii) that different methods should not be used interchangeably, and, iii) that it may be more appropriate to develop gestation-specific ranges for each technique (Masini et al, 2019). In the case of the Modelflow® method, ̇ was non-physiological in some cases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the definitions of FGR and pre-eclampsia vary from study to study. Within this heterogeneous milieu of techniques and definitions, the results of studies on maternal haemodynamic changes using different methodologies are not easily generalizable [8,9], and true relationships may be obscured.…”
Section: Introductionmentioning
confidence: 99%
“…We used three different techniques for cardiovascular assessment in pregnancy, based on inert gas rebreathing [10,11], continuous Doppler [12,13] and impedance cardiography [14]. These techniques cannot be used interchangeably [9], so we have adjusted the maternal cardiovascular results in relation to the gestational week, based on technique-specific healthy controls. Our hypothesis is that increased maternal peripheral vascular resistance and reduced maternal cardiac output are associated with Doppler changes in the fetal circulation, denoting progressively worsening hypoxia.…”
Section: Introductionmentioning
confidence: 99%